Mechanoluminescence from highly transparent ZGO:Cr spinel glass ceramics - Cao, J. I. A. N. G. K. U. N.; Ding, Y. I. C. O. N. G.; Sajzew, R. O. M. A. N.; Sun, M. I. N. G. H. U. I.; Langenhorst, F. A. L. K. O.; Wondraczek, Lothar (Optical Materials Express, 2022)
Light emission in response to mechanical stimulation-termed mechanoluminescence (ML)-enables the optical detection and visualization of mechanical strain. In particular, materials with ML response in the transmission window of aqueous media or biological tissue enable in situ stress level monitoring, biophysical imaging or mechanically induced light delivery. However, most of today’s ML materials are polycrystalline ceramics or ceramic particle composites, which puts constraints on their bulk processability, material homogeneity and optical transparency. Here, we demonstrate ML from highly transparent glass ceramics comprising of a high-volume fraction of extraordinarily small Cr3+-doped ZnGa2O4 (ZGO) crystals embedded in a binary potassium germanate glass matrix. The ZGO phase is precipitated directly from the precursor glass by homogeneous nucleation in a narrow temperature window; entropic phase separation and a self-limited crystal growth rate yield a crystal number density above 1023 m−3. The residual glass matrix encapsulates these crystals in a dense, highly homogeneous material, whereby the microstructural stability and the extended supercooling range of the glass enable glass-like processing, for example, in the shapes of fiber, beads or microspheres.
CRIS-Team Scopus Importer:2023-04-20